Evaluating the Effectiveness of Employee Development Programs: Measuring Impact on Retention and Job Satisfaction - Hendarti, Ricca; Leni Gustina, Romi Susanto, (Pascasarjana STIE Amkop Makassar, 2024)
This study examines the relationships between Employee Development Programs Job Satisfaction, Employee Engagement , and Employee Retention at PT. Anugerah Duta Sari. A quantitative research design utilizing total sampling was employed, with data collected from 70 employees. Path analysis was conducted using Smart PLS to evaluate direct and indirect effects among the variables. Results indicated significant positive effects of Employee Development Programs Job Satisfaction, Employee Engagement, and Employee Retention, and the mediating role of Employee Engagement between Employee Development Programs and ER Employee Retention was confirmed. Additionally, Job Satisfaction significantly influenced EE, which, in turn, affected ER. However, the direct effect of Job Satisfaction on ER was not significant, suggesting that while Job Satisfaction is important, it must be complemented by engagement strategies to enhance retention. The findings emphasize the importance of integrating Employee Development Programs and Job Satisfaction to foster a supportive work environment that enhances employee loyalty and retention. This research provides valuable insights for organizations aiming to improve their human resource practices and develop a committed workforce. Keywords: Employee Development Programs, Job Satisfaction, Employee Engagement, Employee Retention